STRATEGI BELAJAR MNEMONIC DALAM MENGUATKAN DAYA INGAT SISWA PADA MATA PELAJARAN FIQIH KELAS V MADRASAH IBTIDAIYAH - Arif, Muhamad (Journal Of Islamic Elementary School (JIES), 2018)
This paper will describe the perspective of the 21st century era in the world of education, especially in learning, which requires strategies in achieving learning goals. Especially in the study of jurisprudence in a field of Shari'a, in which it clearly discusses various laws to regulate human life, but in this paper it is focused on class V learning of Madrasah Ibtidaiyah. mnemonic for example becomes a solution in learning to help memory performance in students, and can optimize memory performance. Due to the Hajj material in class V the Madrasah Ibtidaiyah has several sections and requires a deeper understanding of this material.